Increased Synaptic Strength and mGlu2/3 Receptor Plasticity on Mouse Prefrontal Cortex Intratelencephalic Pyramidal Cells Following Intermittent Access to Ethanol. (9th February 2021) - Joffe, Max E.; Winder, Danny G.; Conn, P Jeffrey
Abstract : Background: The medial prefrontal cortex (PFC) is crucial for regulating craving and alcohol seeking in alcohol use disorder (AUD) patients and alcohol seeking in animal models. Maladaptive changes in volitional ethanol (EtOH) intake have been associated with PFC function, yet synaptic adaptations within PFC have not been consistently detected in voluntary drinking rodent models. At least 80% of the neurons in PFC are glutamatergic pyramidal cells. Pyramidal cells provide the predominant cortical output to several brain regions relevant to AUD, including structures within the telencephalon (IT: e.g., basal ganglia, amygdala, other neocortical regions) and outside the telencephalon (ET: e.g., lateral hypothalamus, midbrain monoaminergic structures, thalamus). Methods: In addition to their anatomical distinctions, studies from several laboratories have revealed that prefrontal cortical IT and ET pyramidal cells may be differentiated by specific electrophysiological parameters. These distinguishable parameters make it possible to readily classify pyramidal cells into separable subtypes. Here, we employed and validated the hyperpolarization sag ratio as a diagnostic proxy for separating ET (type A) and IT (type B) neurons. We recorded from deep‐layer prelimbic PFC pyramidal cells of mice 1 day after 4 to 5 weeks of intermittent access (IA) EtOH exposure. Results: Membrane properties were not altered by IA EtOH, but excitatory postsynaptic strength onto IT type B neurons was selectively enhanced in slices from IA EtOH mice. The increased excitatory drive was accompanied by enhanced mGlu2/3 receptor plasticity on IT type B neurons, providing a potential translational approach to mitigate cognitive and motivational changes to PFC function related to binge drinking. Conclusions: Together, these studies provide insight into the specific PFC neurocircuits altered by voluntary drinking. In addition, the findings provide an additional rationale for developing compounds that potentiate mGlu2 and/or mGlu3 receptor function as potential treatments for AUD. Abstract : Our understanding of how alcohol affects the prefrontal cortex remains incomplete. Here, Joffe et al. validated and utilized a functional approach to demarcate pyramidal cells based on projection target in mice. After intermittent access to ethanol, potentiated excitatory synaptic strength and enhanced metabotropic glutamate receptor function were observed specifically in intratelencephalic neurons. These findings highlight striking adaptations to prefrontal physiology induced by chronic drinking and support evaluating modulators of mGlu2 and mGlu3 receptors as novel treatments for AUD.